2015
DOI: 10.1103/physrevd.91.014013
|View full text |Cite
|
Sign up to set email alerts
|

Transverse single-spin asymmetries inppγXfrom quark-gluon-quark correlations in the proton

Abstract: We analyze the transverse single-spin asymmetry in direct photon production from proton-proton collisions, denoted A γ N , within collinear twist-3 factorization. We provide a calculation of the contribution due to quark-gluon-quark correlations in the unpolarized proton as well as summarize previous studies on those effects in the polarized proton. Both soft-gluon poles and soft-fermion poles are considered. From this complete result we then estimate A γ N , including error bands due to uncertainties in the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 120 publications
(230 reference statements)
0
29
0
Order By: Relevance
“…[17,21,23,45,46,47,48,49,50,51]. There are a few pieces of A γ N that enter from the side of the incoming protons 2 : (1) the (soft-gluon pole (SGP) chiral-even) QS function, (2) soft-fermion pole (SFP) chiral-even quarkgluon-quark functions, (3) SGP and SFP quark-gluon-quark chiral-odd functions, and (4) SGP 1 In the CT3 framework the Sivers-type (QS) piece, due to the sign mismatch, gives a contribution that is opposite to the data (and in fact small in magnitude) if one uses the Sivers function from SIDIS.…”
Section: Phenomenological Results Formentioning
confidence: 99%
See 1 more Smart Citation
“…[17,21,23,45,46,47,48,49,50,51]. There are a few pieces of A γ N that enter from the side of the incoming protons 2 : (1) the (soft-gluon pole (SGP) chiral-even) QS function, (2) soft-fermion pole (SFP) chiral-even quarkgluon-quark functions, (3) SGP and SFP quark-gluon-quark chiral-odd functions, and (4) SGP 1 In the CT3 framework the Sivers-type (QS) piece, due to the sign mismatch, gives a contribution that is opposite to the data (and in fact small in magnitude) if one uses the Sivers function from SIDIS.…”
Section: Phenomenological Results Formentioning
confidence: 99%
“…The natural assumption has been that (1) is dominant, but there is no reason a priori that (2), (3) cannot give a large asymmetry. Therefore, in [51] we analyzed numerically (1), (2), (3) in order to determine what is the main source of A γ N , and we refer the reader to that paper for details on the phenomenology. The results of this study are shown in Fig.…”
Section: Pos(qcdev2015)011mentioning
confidence: 99%
“…These identities have not only been routinely used in phenomenology (see, e.g., Refs. [59,60,63,64,65]), but also give important physical interpretations of these functions as being connected to average parton transverse momentum [71]. However, these important connections actually break down within the original CSS formalism discussed in Sec.…”
Section: Relations Between Collinear and Tmd Functionsmentioning
confidence: 99%
“…However, since the individual terms in (2.1) add together and cannot be "projected out", one must try to isolate certain pieces through experiments that are only mainly sensitive to a specific function or functions. For example, if one looks at direct photon production, which eliminates the third term in (2.1) since there is no fragmentation, we find such a process is dominated by a quark-gluon-quark PDF, the Qiu-Sterman (QS) function F FT (x, x) [59,60]. The QS function has an important, model-independent relation to the TMD Sivers function [57] f ⊥ 1T (x, k 2 T ) that enters SSAs in processes like semi-inclusive deep-inelastic scattering (SIDIS) and Drell-Yan (DY), which we will cover in Sec.…”
Section: Ssas Within Collinear Factorizationmentioning
confidence: 99%
“…Search for flavour changing neutral currents in the single top association with a 2 Advances in High Energy Physics photon at the LHC has been studied in [9]. In the same sign top quark production at the LHC the top FCNC couplings have been studied in [10]. The top FCNC couplings at future circular hadron electron colliders have been studied in [11].…”
Section: Introductionmentioning
confidence: 99%